Implementation of Social Studies in The Establishment of Social Behavior Students SMP Negeri 1 Brangsong - Indriastuti, Diana; Pramono, Suwito Eko; Suhandini, Purwadhi (JESS (Journal of Educational Social Studies), 2018)
IPS as an integrated subject in the 2013 curriculum aims to develop the potential of learners to become citizens who have the attitude, skills, and knowledge as stock in the life of society. The purpose of this study are (1) describe and analyze the implementation of IPS education in social studies in SMP N 1 Brangsong, (2) describe and analyze the IPS learning can shape the social behavior of students in SMP N 1 brangsong, (3) describe and analyze the obstacles of the implementation of learning IPS in shaping the social behavior of students in SMP N 1 Brangsong. The result of the research shows that (1) implementation of IPS education in IPS learning in accordance with the curriculum in 2013 by IPS teachers in SMP N 1 Brangsong covers the planning of the teachers covering the study of KI and KD, preparation of lesson plan, materials and media and learning method. In the implementation of learning, teachers use cooperative learning methods and become facilitators for students. Evaluations include daily reassessment, UTS, UAS, UKK as well as student ratings. (2) social behavior of 8th grade students of SMP N 1 Brangsong is good, because it has applied social values ​​from IPS learning in schools such as the value of tolerance, protect the environment. Form of implementation of IPS scores by students such as helping friends, obeying school rules, maintaining the environment. (3) barriers to the implementation of social studies in the formation of social behavior of students of SMP N 1 Brangsong is the not optimal socialization of the 2013 curriculum, RPP format, attitude assessment, and IPS material too much. The conclusions of this study indicate that the implementation of ips learning in the formation of social behavior that is generally social behavior of 8th grade students of SMP N 1 Brangsong in good category.